In situ nanoindentation method for characterizing tensile properties of AISI 1045 steel based on mesomechanical analysis. (July 2019) - Li, Cong; Zhao, Hongwei; Sun, Linlin; Yu, Xiujuan
A novel method for characterizing the tensile properties of AISI 1045 steel is proposed by combining the method of in situ nanoindentation test and the theory of mesomechanical analysis. First, the load–depth curves of exact location of ferrite, pearlite and grain boundary on the surface of AISI 1045 steel are obtained by 30 groups of in situ nanoindentation tests. The constitutive equation (stress–strain function) of the real-time metallographic structure is obtained by nanoindentation analysis of the above curves. Then, based on the principle of mesomechanical analysis, the computational representative volume element models are reconstructed according to the three metallographic images of AISI 1045 steel surface collected by the test equipment. Finally, taking the constitutive equation of the real-time metallographic structure as the input condition, the finite element analysis of the above representative volume element models are carried out. The data resulted from finite element analysis are taken as the tensile mechanical properties of AISI 1045 steel. The elastic modulus of AISI 1045 steel calculated is as the same as that by the traditional nanoindentation method. And, the error is less than 6% compared with the tensile test, which is within the range of the elastic modulus of the material. The error between the yield strength calculated and tensile test results is 3.4%. Due to the influence of surface cracks on the plastic deformation ability of AISI 1045 steel during tension, the error between the strain hardening index calculated and tensile test results is 7.4%. The results show that it is a more accurate nondestructive testing method in the point of material damage mechanism. On the premise of using more accurate representative volume element modelling way, this method is suitable for testing more materials.